2004
DOI: 10.1007/s00221-003-1717-9
|View full text |Cite
|
Sign up to set email alerts
|

When pros become cons for anti- versus prosaccades: factors with opposite or common effects on different saccade types

Abstract: In five experiments we compared prosaccade and antisaccade performance in normal human observers. This was first examined for visual stimulation in temporal or nasal hemifields, under monocular viewing. Prosaccades were faster following temporal than nasal stimulation, in accordance with previous results. The novel finding was that the opposite pattern was observed for antisaccades, consistent with a difficulty in overcoming a stronger prosaccade tendency after temporal-hemifield stimulation. A second experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
67
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 58 publications
11
67
2
Order By: Relevance
“…Figure 5 shows that, while prosaccades become faster when the target has a higher strength, antisaccades are slowed down. This is in line with findings from Kristjánsson et al (2004). These authors also found that for very low-contrast targets, both pro-and antisaccades became slower.…”
Section: Antisaccadessupporting
confidence: 89%
See 2 more Smart Citations
“…Figure 5 shows that, while prosaccades become faster when the target has a higher strength, antisaccades are slowed down. This is in line with findings from Kristjánsson et al (2004). These authors also found that for very low-contrast targets, both pro-and antisaccades became slower.…”
Section: Antisaccadessupporting
confidence: 89%
“…This simulation Kristjánsson et al (2004) showed that the lack of inhibition resulted in mostly erroneous prosaccades to the onset location. When no prosaccade was made, antisaccades tended to be very slow as the resolution of competition between the pro-and antisaccade goal took very long.…”
Section: Antisaccadesmentioning
confidence: 87%
See 1 more Smart Citation
“…In a follow-up study, Kristjánsson et al (2004) demonstrated that certain manipulations had opposite effects on prosaccades and antisaccades, which provided further evidence for the competition account of antisaccade generation.…”
mentioning
confidence: 78%
“…However, several findings from Kristjánsson and colleagues (Kristjánsson, 2007;Kristjánsson et al, 2001;Kristjánsson et al, 2004) have provided evidence for the view that prosaccades and antisaccades are not programmed independently, but instead compete interactively. For example, Kristjánsson et al (2001) showed that when attending to a secondary task (a peripheral discrimination task) shortly before the presentation of the antisaccade stimulus, latencies were increased in the prosaccade task but reduced in the antisaccade task.…”
mentioning
confidence: 99%